The analysis of foreign experience and Russian practices of changing the role of nurses - Yulia V. Burdastova (Здоровье мегаполиса)
The article provides an overview of the European experience in changing the role of a nurse, as well as Russian practices within the framework of a pilot project to expand the functions of nurses in accordance with the order of the Ministry of Health of Russia «On the approval of an action plan («road map») to expand the functions of specialists with secondary medical education. The author emphasizes that the new challenges of the millennium entail a shift in emphasis towards patient orientation, which implies an improvement in the quality of medical services, and this, in turn, will address the issues of competent distribution of powers between doctors and nurses. The article notes that patient-centered medical care entails an increase in the burden on nurses and their empowerment. The author analyzes both the advantages of expanding the role of nurses: career advancement with continuous professional and personal development through the acquisition of additional knowledge and competencies, and possible risks: psychological resistance of doctors and nurses to new forms of work, conflict of interests between doctors and nurses, unwillingness of nurses to work with documents, etc.